Prophylactic Strategy Against De Novo Hepatitis B Virus Infection for Pediatric Recipients Who Receive Hepatitis B Core Antibody–Positive Liver Grafts. Issue 1 (1st December 2020) - Song, Zhuolun; Dong, Chong; Meng, Xingchu; Sun, Chao; Wang, Kai; Qin, Hong; Han, Chao; Yang, Yang; Zhang, Fubo; Zheng, Weiping; Chen, Jing; Duan, Keran; et al.
Abstract : The goal of this study was to evaluate the efficacy of a perioperative prophylactic strategy against de novo hepatitis B virus (HBV) infection in pediatric liver transplantation (LT) recipients with hepatitis B core antibody (HBcAb)–positive grafts. A total of 482 pediatric recipients transplanted between 2013 and 2017 were enrolled, and 170 recipients received HBcAb‐positive liver grafts. The overall graft and recipient survival rates in HBcAb‐positive and HBcAb‐negative graft recipients were 91.8% versus 91.3% and 95.3% versus 94.2% at the end of follow‐up. Preoperative hepatitis B surface antibody (HBsAb) titer ≥ 1000 IU/L and postoperative HBsAb titer ≥200 IU/L were our prophylactic targets for recipients receiving HBcAb‐positive grafts. While 11 recipients developed de novo HBV infection, 10 received HBcAb‐positive grafts. Both the preoperative and postoperative HBsAb targets were achieved in 78 recipients, the infection rate of de novo HBV was 1.3%; 24 recipients met the preoperative target, the infection rate was 4.2%; 52 recipients met the postoperative target, the infection rate was 1.9%; and 16 recipients met neither the preoperative nor postoperative HBsAb target, 43.8% of the recipients were infected with de novo HBV, which was significantly higher than the recipients who met both or either of the preoperative and postoperative targets. Split‐liver grafts positive for HBcAb showed higher risk of de novo HBV infection. Postoperative application of lamivudine to recipients whose preoperative HBsAb titer < 1000 IU/L did not show preventive effect. Out of 11 infected recipients, 3 showed seroconversion under entecavir treatment. In conclusion, the graft and recipient survival rates were similar in pediatric LT recipients receiving HBcAb‐positive or HBcAb‐negative grafts. Our prophylactic strategy was effective for preventing de novo HBV infection in HBcAb‐positive liver graft recipients.